Investigation of the effects of some antibiotics and vitamin A on the polymorphonuclear leukocyte functions of neutropenic children - (:unkn) unknown (My University, 2007)
In this study the in vitro effects of imipenem, cefodizime, vancomycin, teicoplanin, imipenemamikacin, imipenem-teicoplanin combinations and vitamin A at therapeutic concentration on phagocytic and intracellular killing activity of polymorphonuclear leukocytes (PMNs) in neutropenic children with acute leukemia were investigated. Twenty-one neutropenic children with mean age 7 were included in this study and were clinically divided in 3 groups. The first group included 7 nonfebrile neutropenic children not receiving chemotherapy; the second group included 7 febrile neutropenic children receiving chemotherapy; the third group included 7 nonfebrile neutropenic children receiving chemotherapy. PMNs were isolated by Ficoll-Hypaque gradient centrifugation method. C. albicans ATCC 10231 was used to measure the phagocytosis and intracellular killing activity of PMNs. Consequently, in the 1st group; the antibiotics used in our investigation and vitamin A significantly increased PMN's phagocytic activity, cefodizime showed immunomodulatory effect on the both PMN functions in the 1st and 2st group. Additionally, vancomycin had immunomodulatory effect on the both PMN functions in the 1st group and only on the phagocytic activity in 3rd group.
Keywords: Antibiotic; Intracellular killing; Neutropenia; Phagocytosis; Polymorphonuclear leukocyte; Vitamin A